Electromagnetic monitoring in seismically active regions of Siberia - Nevedrova, N. N.; Epov, M. I. (Geofizicheskiy Zhurnal, 2012)
Field data of the electromagnetic monitoring of controlled source have been obtained in two seismically active regions of Siberia. The article demonstrates an approach to the interpretation of regime observations data and it attempts to explain the variation of the electromagnetic parameters due to geodynamic processes, taking into account the peculiarities of the nontectonic structure. For the territory of the Baikal polygon, which is located on the southwestern shore of the Baikal Lake, geoelectric characteristics of the main seismogenic structures and fault disturbances have been provided. The analysis of monitoring measurements interpretation at constant current in the regime point VES has been presented and the relationship with the geoelectric structure has been proved; the sensitivity of the VES setting was determined. In the Altai geodynamic polygon the measurements were conducted by a complex of electromagnetic methods (VES, TEM in several modifications). The investigations were aimed at the study of a structure and variations of electrical conductivity associated with the devastating Chui earthquake and development of aftershock process. Interpretation of the regime TEM data with an inductive source has been considered. On the basis of the complex geologo-geophysical analysis the processes of geological array consolidation disturbed by the strong seismic influence have been described.